Recent trends in cerebral palsy survival. Part II: individual survival prognosis. (12th July 2014) - Brooks, Jordan C; Strauss, David J; Shavelle, Robert M; Tran, Linh M; Rosenbloom, Lewis; Wu, Yvonne W
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to determine survival probabilities and life expectancies for individuals with cerebral palsy based on data collected over a 28‐year period in California. Method We identified all individuals with cerebral palsy, aged 4 years or older, who were clients of the California Department of Developmental Services between 1983 and 2010. Kaplan–Meier survival curves were constructed for 4‐year‐old children, and the estimated survival probabilities were adjusted to reflect trends in mortality by calendar year. For persons aged 15, 30, 45, and 60 years, separate Poisson regression models were used to estimate age‐, sex‐, and disability‐specific mortality rates. These mortality rates were adjusted to reflect trends of improved survival, and life expectancies were obtained using life table methods. Results The sample comprised 16 440, 14 609, 11 735, 7023, and 2375 persons at ages 4, 15, 30, 45, and 60 years, respectively. In 1983, 50% of 4‐year‐old children who did not lift their heads in the prone position and were tube fed lived to age 10.9 years. By 2010, the median age at death had increased to 17.1 years. In ambulatory children the probability of survival to adulthood did not change by more than 1%. Life expectancies for adolescents and adults were lower for those with more severe limitations in motor function and feeding skills, and decreased with advancing age. Life expectancies for tube‐fed adolescents and adults increased by 1 to 3 years, depending on age and pattern of disability, over the course of the study period. Interpretation Over the past three decades in California there have been significant improvements in the survival of children with very severe disabilities. There have also been improvements to the life expectancy of tube‐fed adults, though to a lesser extent than in children.